Synergistic effects of mutation and glycosylation on disease progression - Suzuki, Shodai; Itoh, Motoyuki (Frontiers in Molecular Biosciences, 2025)
Glycosylation, a post-translational modification, plays a crucial role in proper localization and function of proteins. It is regulated by multiple glycosyltransferases and can be influenced by various factors. Inherited missense mutations in glycosylated proteins such as NOTCH3, Low-density lipoprotein receptor (LDLR), and Amyloid precursor protein (APP) could affect their glycosylation states, leading to cerebral small vessel disease, hypercholesterolemia, and Alzheimer’s disease, respectively. Additionally, physiological states and aging-related conditions can affect the expression levels of glycosyltransferases. However, the interplay between mutations in glycosylated proteins and changes in their glycosylation levels remains poorly understood. This mini-review summarizes the effects of glycosylation on transmembrane proteins with pathogenic mutations, including NOTCH3, LDLR, and APP. We highlight the synergistic contributions of missense amino acids in the mutant proteins and alterations in their glycosylation states to their molecular pathogenesis.